2022
DOI: 10.1021/jacs.2c07377
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Pyridine Aromatization during Thiopeptide Biosynthesis

Abstract: Thiazole-containing pyritides (thiopeptides) are ribosomally synthesized and post-translationally modified peptides (RiPPs) that have attracted interest owing to their potent biological activities and structural complexity. The class-defining feature of a thiopeptide is a six-membered, nitrogenous heterocycle formed by an enzymatic [4 + 2]-cycloaddition. In rare cases, piperidine or dehydropiperidine (DHP) is present; however, the aromatized pyridine is considerably more common. Despite significant effort, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…These results highlight the remarkable substrate-level cooperativity of Laz enzymesespecially when it comes to modifying C/S/T-rich local environmentsconsidering that the pattern of C/S/T residues in w7 and other discovered sequences bears no resemblance to that of wild-type LazA. Despite the extensive efforts to unravel the substrate recruitment and discrimination by Laz and related RiPP enzymes, , our understanding of such a promiscuous (deep modification of random inserts) but at the same time selective (formation of one or at most a few products) processing of precursor peptides is lacking. Altogether, we narrowed our focus to 18 sequences which furnished mostly homogeneous thiopeptides (seven from the library v.t.4h and 11 from v.t.4w) for the following experiments.…”
Section: Resultsmentioning
confidence: 96%
“…These results highlight the remarkable substrate-level cooperativity of Laz enzymesespecially when it comes to modifying C/S/T-rich local environmentsconsidering that the pattern of C/S/T residues in w7 and other discovered sequences bears no resemblance to that of wild-type LazA. Despite the extensive efforts to unravel the substrate recruitment and discrimination by Laz and related RiPP enzymes, , our understanding of such a promiscuous (deep modification of random inserts) but at the same time selective (formation of one or at most a few products) processing of precursor peptides is lacking. Altogether, we narrowed our focus to 18 sequences which furnished mostly homogeneous thiopeptides (seven from the library v.t.4h and 11 from v.t.4w) for the following experiments.…”
Section: Resultsmentioning
confidence: 96%
“…52 Recent studies demonstrated that a tyrosine residue in the active site of a pyritide synthase in the thiopeptide pathway facilitates the nal aromatization step of pyridine formation. 53 Many RiPPs contain D-amino acid residues. Recent studies demonstrated that a F420-dependent reductase in the biosynthesis of lexapeptide 6 catalyses an iterative biotransformation, changing the corresponding Dha residues to D-Ala in a stereo-specic manner.…”
Section: Reviewmentioning
confidence: 99%
“… 52 Recent studies demonstrated that a tyrosine residue in the active site of a pyritide synthase in the thiopeptide pathway facilitates the final aromatization step of pyridine formation. 53 …”
Section: Dhaas In Ribosomal Peptides and Proteinsmentioning
confidence: 99%